2018
DOI: 10.5267/j.uscm.2017.7.001
|View full text |Cite
|
Sign up to set email alerts
|

A three-phase heuristic approach to solve an integrated cell formation and production planning problem

Abstract: In today's dynamic business environment, the product mix and demand may vary from period to period. Therefore, the same configuration of cellular systems will not be optimal in different periods. In this paper, a new mixed integer non-linear mathematical programming model is presented to design dynamic cellular manufacturing systems and combines several design features including multi-period production planning, alternate routings, system reconfiguration, duplicate machines, lot splitting, workload balance amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Further, it has been found that the proposed heuristic algorithm provided a better optimal solution in less computational time. Kheirkhah and Ghajari (2018) proposed a three-phase heuristic algorithm to solve the problem of cellular manufacturing systems and production planning. Further, optimal solutions and computational efficiency were analyzed.…”
Section: Literature Surveymentioning
confidence: 99%
“…Further, it has been found that the proposed heuristic algorithm provided a better optimal solution in less computational time. Kheirkhah and Ghajari (2018) proposed a three-phase heuristic algorithm to solve the problem of cellular manufacturing systems and production planning. Further, optimal solutions and computational efficiency were analyzed.…”
Section: Literature Surveymentioning
confidence: 99%
“…Flexible manufacturing and heuristic algorithms are two motor themes that were instrumental in defining the field's structure during the initial period. Numerous authors have favored the use of heuristic or meta-heuristic algorithms over mathematical modeling when it comes to solving large CMS problems (Kheirkhah and Ghajari, 2018). Ballakur and Steudel (1987) concluded that the heuristic outperforms multiple criteria.…”
Section: Conceptual Structurementioning
confidence: 99%
“…This avoids the need for a lot of manual water pattern design work, so only a small number of base water patterns need to be designed according to the musical style. Hidden Markov models also applied to chord classification, but they are special in that the observed distribution is no longer based on the given training data set, considering the influence of higher harmonics, using music theory knowledge as a reference for constructing the observation distribution and suggesting that the weight share of fifth-degree chords has more influence compared to third-degree chords [ 10 ]. The final improved model structure and observation distribution allow it to reach 76% in terms of recognition accuracy.…”
Section: Related Workmentioning
confidence: 99%